1967
DOI: 10.1136/oem.24.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Pulmonary Mechanics in Arc Welders' Siderosis

Abstract: Sixteen working welders with more than seven years' exposure and a chest radiograph suggestive of siderosis and I3 healthy unexposed men were studied. Each subject had a comprehensive medical and work history, physical examination, standard chest film, and pulmonary function investigation (lung volumes, ventilatory capacities, pulmonary compliance in static and dynamic conditions, specific compliance, and elastic work of breathing).Seven of the welders had some exertional dyspnoea and three complained of cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1967
1967
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(1 reference statement)
0
5
1
Order By: Relevance
“…18 The study indicated that sustained exposure to iron oxide, which in the present instance averages 18.7 years, did not produce in the welders clinical and physiological findings that were significantly different from those of the control group. There was a moderate prevalence of positive radiological findings characterized by reticulonodular shadowing in the overall group of welders, with a greater percentage of these findings in those exposed over 20 years…”
Section: Inert Reaction Siderosiscontrasting
confidence: 52%
See 1 more Smart Citation
“…18 The study indicated that sustained exposure to iron oxide, which in the present instance averages 18.7 years, did not produce in the welders clinical and physiological findings that were significantly different from those of the control group. There was a moderate prevalence of positive radiological findings characterized by reticulonodular shadowing in the overall group of welders, with a greater percentage of these findings in those exposed over 20 years…”
Section: Inert Reaction Siderosiscontrasting
confidence: 52%
“…Histological findings in a deceased 61-year-old asbestos insulator exposed to asbestos dust for18 years. (A) Interstitial fibrosis with dust particles absorbed into the macrophages.…”
mentioning
confidence: 99%
“…In formation of the welders' lungs, the content of the source of smoke, the working environment (closed area, ventilation status, other exposures in the workplace), personal factors (use of protective materials, smoking) play important role (7,8). In this study the most of the welders were working in shipyard, so they were also exposed to processes such as paint, asbestos and scraper.…”
Section: Discussionmentioning
confidence: 99%
“…Welders' lung is a result of mixed inhalant exposures that effect airways and parenchyma together. Long-term exposure may result welders' lung (benign pneumoconiosis/siderosis) (7)(8)(9). Siderozis has widespread bilateral poorly defined centrilobular nodules and branched small linear opacities but not fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The condition became known as welders' siderosis and for many years most published reports suggested that the condition was harmless, with no impairment of general health or respiratory function. Stanescu et al (1967) summarized these reports but listed some more recent papers which had questioned this view and described their own study. Comparing welders who had chest radiographs suggestive of siderosis with healthy unexposed men, they found that although spirographic values were generally within normal range, the arc welders had a statistically significant reduction in static and functional compliance.…”
mentioning
confidence: 99%